2019
DOI: 10.1016/j.radi.2018.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Personnel flux and workplace anxiety: Personal and interpersonal consequences of understaffing in UK ultrasound departments

Abstract: Do w nlo a d e d fro m: h t t p://i n si g h t. c u m b ri a. a c. u k/i d/ e p ri n t/ 4 0 3 2/ U s a g e o f a n y i t e m s f r o m t h e U n i v e r s i t y o f C u m b r i a' s i n s t i t u t i o n a l r e p o s i t o r y 'I n s i g h t' m u s t c o n f o r m t o t h e f o l l o w i n g f a i r u s a g e g u i d e l i n e s .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The study by Daugherty, 15 sampling 113 sonographers, reported higher levels of EE and lower levels of PA for participants who worked in hospital settings compared to private settings. Similarly, the sample population of 20 in the study by Miller et al 19 was composed of 90% hospital workers, as were the entire sample population of 100 in the study by Craig et al 1 with both studies finding stress and burnout were a significant problem for sonographers, although both studies highlighted workload as the cause. These findings may suggest that the workplace setting further contributes to the likelihood of burnout although more research in this area is needed.…”
Section: Settingmentioning
confidence: 95%
See 1 more Smart Citation
“…The study by Daugherty, 15 sampling 113 sonographers, reported higher levels of EE and lower levels of PA for participants who worked in hospital settings compared to private settings. Similarly, the sample population of 20 in the study by Miller et al 19 was composed of 90% hospital workers, as were the entire sample population of 100 in the study by Craig et al 1 with both studies finding stress and burnout were a significant problem for sonographers, although both studies highlighted workload as the cause. These findings may suggest that the workplace setting further contributes to the likelihood of burnout although more research in this area is needed.…”
Section: Settingmentioning
confidence: 95%
“…A summary of these papers can be seen in type of research undertaken across these seven papers varied significantly. Three studies exposed potential causes of burnout utilising cross-sectional surveys, 15,16,20 two studies used semi-structured interviews 1,19 and two were opinion pieces. 4,21 Sample sizes also greatly varied between the articles, with the two opinion pieces reflecting the opinion of a single sonographer and therefore a sample size of 1, to the more robust sample size of 121 utilised in the crosssectional study by Singh et al 16…”
Section: Potential Causes Of Burnoutmentioning
confidence: 99%
“…We would like to congratulate Mitchell, Nightingale and Reeves for their article on 'Competence to capability: An integrated career framework for sonographers' for providing a suggested framework for skills escalation for sonographers 1 . This is particularly relevant to the current work being undertaken by Health Education England (HEE) to attempt to address the sonographer shortages in England 2 and challenges faced by the introduction of a wider range of entry points to ultrasound practice 3,4 .…”
Section: Dear Editormentioning
confidence: 99%
“…In addition, it could be assumed that turnover and personnel shortage affect workers' ability to maintain a satisfactory level of performance [18,19]. In turn, this adversely affects job satisfaction in particular, and well-being in general [16,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%